2017
DOI: 10.1002/ceat.201700098
|View full text |Cite
|
Sign up to set email alerts
|

Performance Testing of Hydrodesulfurization Catalysts Using a Single‐Pellet‐String Reactor

Abstract: Dedicated to Professor Rüdiger Lange on the occasion of his 65th birthday Small-scale parallel trickle-bed reactors were used to evaluate the performance of a commercial hydrodesulfurization catalyst under industrially relevant conditions. Catalyst extrudates were loaded as a single string in reactor tubes. It is demonstrated that product sulfur levels and densities obtained with the single-pelletstring reactor are close to the results obtained in a bench-scale fixed-bed reactor operated under the same conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 14 publications
0
16
0
Order By: Relevance
“…[ 20 ] Despite this low ratio, SPSRs' mass transfer performance for gas/solid and gas/liquid/solid reactions is good. [ 20,29,30 ] In addition, in the case of gas/liquid flow, a Taylor flow pattern develops, which might account for the unexpected improvement of heat transfer properties. [ 20 ]…”
Section: Descriptionmentioning
confidence: 99%
See 3 more Smart Citations
“…[ 20 ] Despite this low ratio, SPSRs' mass transfer performance for gas/solid and gas/liquid/solid reactions is good. [ 20,29,30 ] In addition, in the case of gas/liquid flow, a Taylor flow pattern develops, which might account for the unexpected improvement of heat transfer properties. [ 20 ]…”
Section: Descriptionmentioning
confidence: 99%
“…Avantium N.V. has developed a line of HTCT systems called Flowrence that are built following a general principle but are adaptable to meet the particular needs of each application. [ 30,38,39 ] A 16‐reactor Flowrence unit (Figure 4), for example, has a common diluent gas section and a separate common mixed feed gas manifold. The gases feed to 16 inlet tubes together with a liquid injected through a single manifold.…”
Section: Descriptionmentioning
confidence: 99%
See 2 more Smart Citations
“…String reactors (bead strings or pellet strings etc.) i) provide plug flow behaviour with negligible bypass or axial dispersion 58 , ii) possess efficient heat transfer due to the large surface area to volume ratio 58 , iii) allow the use of similar superficial velocities to those that are used in industrial scale reactors [58][59][60][61] iv) increased reproducibility between reactors as packing is always uniform 58,59 v) ease of scale-up through parallelisation 62 and vi) they use industrial sized catalyst pellets instead of smaller particles or powders, hence allowing the study of any catalyst pellet skin effects 63 In order to confirm that the reactor behaved as a plug flow reactor, a step change Residence Time Distribution (RTD) study was conducted at four different flowrates in the area of interest for the kinetic study, (10, 20, 40 and 80 µL/min). This RTD study is shown in the Supporting Information, and confirmed that the reactor could be reasonably modelled as a plug flow reactor as the vessel dispersion numbers ranged from 0.01-0.02.…”
Section: Experimental Set-upmentioning
confidence: 99%